EVALUATING THE IMPACT OF AI-DRIVEN QUIZ APPLICATIONS ON EDUCATIONAL OUTCOMES: A CASE STUDY OF WENDIGO - Hammad Naeem; Waseem Tariq; Izaan Ali; Onib-ur-Rehman (Journal of Religion and Society, 2025)
This study examines the impact of AI-driven quiz applications on educational outcomes, with a specific focus on the Wendigo application. In recent educational contexts, the integration of Artificial Intelligence (AI) and Natural Language Processing (NLP) technologies has revolutionized teaching and learning methods, particularly through quiz-based assessments. The Wendigo application utilizes these advancements to enhance user engagement and academic performance, prompting an investigation into its effectiveness across various educational settings. This research employs a mixed-methods approach, combining quantitative data from user interactions with qualitative insights from interviews and case studies. Preliminary results indicate that Wendigo significantly improves student engagement and learning outcomes by providing tailored educational content and real-time feedback. This study contributes to the pedagogical field by demonstrating how AI-driven technologies can be effectively integrated into educational frameworks to support and enhance student learning. Additionally, it addresses the gap in empirical research regarding the direct effects of such technologies on student performance, providing a foundation for future innovations in educational technology. Keywords: AI-Driven Education, Quiz Applications, Educational Outcomes, User Engagement, Natural Language Processing, Educational Technology